Age-and gender-related pattern of methylation in the MT-RNR1 gene. (August 2015) - D'Aquila, Patrizia; Giordano, Marco; Montesanto, Alberto; De Rango, Francesco; Passarino, Giuseppe; Bellizzi, Dina
Aim: We evaluated the methylation of two CpG sites located within human mitochondrial 12S and 16S ribosomal RNA ( MT-RNR1 and MT-RNR2 ) genes.Materials & methods: Methylation was measured through bisulfite sequencing and qPCR assays on DNA samples collected from 381 differently aged human subjects.Results: Analyses revealed the methylation of the site in the MT-RNR1 gene and the co-presence of both unmethylated and methylated cytosines in most samples. High methylation levels (>10%) were more frequent in old women with respect to younger controls. A 9-year-long follow-up survey showed that subjects with high methylation levels exhibit a mortality risk significantly higher than subjects with low levels.Conclusion : Our data further support the presence of methylation within human mitochondrial DNA and suggest that high levels of methylation of the MT-RNR1 site may reflect a condition of the cell or of the organism unfavorable to survival.